Reduced hydrogen sulfide production contributes to adrenal insufficiency induced by hypoxia via modulation of NLRP3 inflammasome activation. (31st December 2023) - Zhang, Ningning; Zhou, Zhan; Huang, Yan; Wang, Gang; Tang, Zhengshan; Lu, Jianqiang; Wang, Changnan; Ni, Xin
ABSTRACT: Objective: Adrenocortical responsiveness is critical for maintaining glucocorticoids production and homeostasis during stress. We sought to investigate adrenocortical responsiveness during hypoxia in mice and the mechanisms responsible for the regulation of adrenal responsiveness. Methods: (1) Adult male WT mice were randomly divided into four groups: normoxia, hypoxia (24h), hypoxia (72h), hypoxia (72h) + GYY4137(hydrogen sulfide (H2 S) donor, 133mmol/kg/day); (2) WT mice were randomly divided into four groups: sham, adrenalectomy (ADX), sham+hypoxia, ADX+hypoxia; (3) Cse -/- mice were randomly divided into two groups: Cse -/-, Cse -/- +GYY4137. Results: The circulatory level of corticosteroid induced by ACTH stimulation was significantly reduced in the mice with hypoxia compared with control mice. The mortality rate induced by lipopolysaccharide (LPS) increased during hypoxia. Cystathionine-γ-lyase (CSE) expression was significantly reduced in adrenal glands during hypoxia. GYY4137 treatment significantly increased adrenal responsiveness and attenuated NLRP3 inflammasome activation in mice treated by hypoxia and Cse -/- mice. Furthermore, The sulfhydrated level of PSMA7 in adrenal gland was decreased in the mice with hypoxia and Cse -/- mice. PSMA7 was S-sulfhydrated at cysteine 70. Blockage of S-sulfhydration of PSMA7 increased NLRP3 expression in adrenocortical cells. Conclusion: Reduced H2 S production mediated hypo-adrenocortical responsiveness and NLRP3 inflammasome activation via PAMA7 S-sulfhydration during hypoxia.